Diagnosis of sorghum production and its market in Côte d’Ivoire - Diby, N’Nan; Mobio, Jacob Aubin; Kanon, Landry Alban; Deffan, Khando Prudence; Sangare, Salimata; N’Da, Hughes Annicet; Bouniol, Alexandre (CGIAR System Organization, 2025)
Sorghum, the fourth most important cereal in Côte d’Ivoire, accounts for approximately 3% of national cereal production, with an annual output exceeding 70,000 tons. Cultivated mainly by smallholder farmers in the northern regions, it serves multiple purposes: human consumption, traditional brewing (local malting), and animal feed. Despite its high nutritional value and resilience to arid conditions, sorghum remains a neglected crop, with consumption steadily declining. This brief evaluates the sorghum value chain based on a literature review and survey data, identifying two main variety types, red sorghum and white sorghum, as well as a lesser-known brown type. Key challenges limiting production and consumption include damage to fields caused by transhumance, as livestock favor sorghum plants and therefore require close monitoring of fields; the tediousness of processing for food applications, particularly grain dehulling; insufficient technical support; the absence of government subsidies; and limited market opportunities for producers. Recommendations to address these bottlenecks include the development of easy-to-process varieties, innovations in processing, stronger government support, and public awareness to promote sorghum as a climate-resilient crop essential for food security and rural development.